2019
DOI: 10.1093/mnras/stz847
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis on habitable planets around low-mass stars

Abstract: We show that planets around M-dwarfs with M 0.2M may not receive enough photons in the photosynthetically active range of 400-750 nm to sustain Earth-like biospheres. As a result of the lower biological productivity, it is likely that biotic molecular oxygen would not build up to detectable levels in the atmospheres of habitable planets orbiting low-mass stars, consistent with prior work by Lehmer et al. (2018). We also estimate the minimum flaring rate for sustaining biospheres with Earth-like productivity a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…This is a rather mild criterion, and will not be anthropically relevant. This would be useful in a more sophisticated analysis that determines the potentially photosynthetic stars by considering when the useful part of their spectrum falls below this threshold along the lines of [63], rather than our somewhat simplified prescription of scaling based off the surface temperature. We do not expect this more elaborate treatment to substantially alter our conclusions.…”
Section: Is Photosynthesis Necessary For Complex Life?mentioning
confidence: 99%
“…This is a rather mild criterion, and will not be anthropically relevant. This would be useful in a more sophisticated analysis that determines the potentially photosynthetic stars by considering when the useful part of their spectrum falls below this threshold along the lines of [63], rather than our somewhat simplified prescription of scaling based off the surface temperature. We do not expect this more elaborate treatment to substantially alter our conclusions.…”
Section: Is Photosynthesis Necessary For Complex Life?mentioning
confidence: 99%
“…However, it was also argued therein that oxygenic photosynthesis might not evolve on planets around M-dwarfs as this process accords minimal competitive advantage. Lehmer et al (2018) investigated whether enough photons would be available to support an Earth-like biosphere on M-dwarf exoplanets, and found that many of them are incapable of doing so; see also Lingam and Loeb (2019d). In particular, if the maximum wavelength of PAR is specified to be 750 nm, none of the TRAPPIST-1 planets in the HZ appear to have the capacity for sustaining Earth-like biospheres.…”
Section: Photosynthesismentioning
confidence: 99%
“…However, an important point worth recognizing is that flares can also deliver photons in the PAR range. Hence, when the effects of stellar flares are included, theoretical calculations seem to indicate that the PAR flux may be raised by approximately one order of magnitude Bais, 2018) (see, however, Lingam andLoeb 2019d), although the averaged photosynthetic efficiency of planets in the HZ of M-dwarfs is still anticipated to be lower than that of the Earth (Scharf, 2019). Finally, the high fluxes of UV radiation incident on the surface during flaring events are expected to result in intermittently enhanced mutation rates, thereby serving as agents of ecological and evolutionary change (Smith et al, 2004b).…”
Section: A Electromagnetic Radiationmentioning
confidence: 99%
“…Life could also develop subsurface (Lingam & Loeb 2019a). More exotic scenarios include biological life in the atmospheres of brown dwarfs (Lingam & Loeb 2019b), or in or around binary stars (Vidal 2016).…”
Section: Other Technological Life Existsmentioning
confidence: 99%